VARIATION OF WATER QUALITY IN NHA TRANG BAY - Thu, Phan Minh; Hieu, Nguyen Trinh Duc; Thao, Pham Thi Phuong (Vietnam Journal of Marine Science and Technology, 2016)
Based on survey data in the period of 2013 - 2015 and historical data between 1996 - 1998, the paper showed the variation of water quality parameters by time. The concentration of total suspended sediment, chlorophyll-a, dissolved inorganic nitrogen, dissolved inorganic phosphorus and ratio of N:P changed significantly by season. The results of assessing water quality by UNTRIX (integrated concentration of Chlorophyll-a, dissolved inorganic nitrogen, dissolved inorganic phosphorus and level of saturated oxygen) indicated the quality levels were increased from meso-eutrophication in 1996 (average UNTRIX: 4.54 ± 0.76) to oligo-eutrophication in the period of 2013 - 2015 (average UNTRIX from 2.62 ± 0.66 to 3.81 ± 0.45).